A New Model of Russian Doctoral Education: Problems and Prospects - B. I. Bednyi; M. B. Sapunov (Высшее образование в России, 2019)
On November 16, 2018, as a part of its Advanced Training Program, the National Research Lobachevsky State University of Nizhny Novgorod (UNN) hosted a round table organized by the UNN Institute of Postgraduate and Doctoral Studies jointly with the editorial board of the journal “Higher Education in Russia”. The topic of the round table discussion was “A New Model of Russian Doctoral Education: Problems and Prospects for Development”. The Program is being implemented in accordance with the UNN’s “Roadmap” for 2018 within the framework of the Russian Academic Excellence Project (the “5-100” Project). The event was attended by 48 administrative, managerial and academic staff members from 24 cities, representing 37 universities and research organizations of the Russian Federation (including NUST MISIS, National Research University Higher School of Economics, UNN, Tomsk Polytechnic University, Samara National Research University, Plekhanov Russian University of Economics, Belgorod National Research University, Ogarev Mordovia State University, Tyumen National Research University, etc.).Moderators of the round table: Director of the UNN Institute of Postgraduate and Doctoral Studies Prof. B.I. Bednyi and the Сhief Editor of the journal «Higher Education in Russia» Prof. M.B. Sapunov.